Pengaruh Pengembangan Sumber Daya Manusia, Lingkungan Kerja dan Gaya Kepemimpinan terhadap Kinerja Prajurit TNI di Ajendam V Brawijaya - Shendy Citra Iswandari; Budi Wahono; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study points to look at the impact of human assets, working environment conditions and authority fashion on the work execution of officers in Ajendam V Brawijaya. The inquire about strategy utilized is quantitative through the utilize of information collection methods within the form of surveys within the shape of Google Frame. The gotten information are analyzed utilizing legitimacy test, unwavering quality test, typicality test, multicollinearity test, variable change test, different relapse test, test T and test F. Inquire about comes about appear that human assets, working environment and administration fashion have a noteworthy impact on the execution of troopers at Ajendam V Brawijaya. In portion, human asset advancement and working conditions have a critical and positive effect on trooper execution. Moreover with administration fashion incorporates a positive and noteworthy impact on trooper execution. This study contributes to understanding the factors that influence soldier performance in the military environment. According to the recommendation, Ajendam V Brawijaya can continue to improve human resource development, create a good working environment and adopt the right leadership style to maximize the performance of soldiers. For future researchers, it is advisable to expand the population and develop sampling techniques and use more diverse references to reinforce research findings. Keywords: Human Resources, Work Environment, Leadership, and Soldier Performance